(untitled) (Fiep Bulletin - online, 2011)
This research aims to trace the profile of growth, nutritional status and motor development of school children of the region bordering the city of Igarapé Miri aged 5 to 10 years, attending the series from literacy to the fourth grade of elementary school. The sample was made with students of both sexes in a total of 53 students: 26 girls (n = 26) and 27 boys (n = 27). The material used to measure the height was a Swordfish - steel tape measure with subdivision 0.1 cm. A digital Day-home-ed-307 scale was used to check the weight, with a platform capacity of 150 kg. Motor development was assessed through the development of extensive test-Moto TGMD2 proposed by Ulrich (2000). The growth curves of the National Center for Health and Statistics’ – NCHS; the nutritional status according the criteria of Waterlow (1976) and the TGMD2 test protocol for motor evaluation were used as reference for analysis of the results for profiles of growth and nutritional status. The results found show a high percentile index below three (<3) revealing a short stature, both for boys and girls, the same result for the nutritional status, 54.71% was selected as malnourished and low index to obesity. In motor assessment both boys and girls showed the average rate higher than expected taking into account the results of the profile of growth and nutritional status specially related to the environment in which they live.